Prinsip-Prinsip Hukum Tentang Yayasan Sebagai Pengelola Lembaga Pendidikan Tinggi Swasta - Ach. Fadlail (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
As a subject of vital human development, plays a central role which will formulate the concept, planning, integrating nodes strength and potential, as well as solve problems that go it. Thus the importance of the role played by humans, it is not exaggeration if humans as subjects of development must truly have personal maturity, good science, capacity, superior capability, and reflects the character of noble character as the embodiment litasnya/its litas. In order to achieve the expected degree of quality, education need the primary human. It may be noted also that one of important aspect of development is education. Regarding at 31 paragraph (1) of the Constitution of the Republic of Indonesia Year 1945 guarantees the right every citizen to get an education. Constitutional mandate is further defined in the legislation under the Constitution. One is Act No. 20 th2003 on Education System National. Primary responsibility of the provision and delivery of education is in the hands of the Government. Folk as education goals, in addition to having the right to education as mandated by the Constitution of the Republic of Indonesia th1945, also bear the responsibility for the implementation of education. Participation and community participation in education which one of them can be done by the foundation.